The importance of green marketing in achieving a new consumer profile in consumer relations (Research, Society and Development, 2020)
The company model that is now established in the market is shaped by a more humanized management, which has changed the consumer's view of the options offered, both in the provision of services and in the supply of products and goods. Since the Eco-92 event, Brazil has turned to environmental issues in a more participatory way, so that the environmental disasters that have occurred in the country - such as the tragedies of Brumadinho and Mariana, in the State of Minas Gerais - have caused great commotion in the country. population and special attention from the Public Power. As a result, the issues of preserving the ecosystem and any bias related to this cause have been gaining a lot of visibility, generating the commitment of large companies to invest in Green Marketing, in the adaptation of products so as not to generate waste and innovation in service provision more sustainable, with the aim of adding social value to the brand and including itself in this market, which tends to grow more and more. The objective of this work is to determine the importance and challenges of implementing Green Marketing in the corporate environment, analyzing the impact caused on consumers. This exploratory and descriptive research aimed at identifying these impacts among consumers and organizations, concluding with the change in approach and sales strategy, especially in relation to the public and its renewed profile, avoiding the techniques used by the company for its social responsibility. maintenance in the new market.